Antibiotic residues in cow's milk - Mimoune, Nora (Array, 2021)
Veterinary treatments, mainly antibiotics, used for therapeutic or prophylactic purposes in dairy cows, may be the cause of the presence of their residues in milk. This can have harmful consequences on animal and human health. To fully understand this problem, the present study aimed to evaluate the presence of antibiotic residues on 160 samples of cow"s milk in the North Central region of Algeria, using two distinct microbiological techniques (acidification test and agar diffusion test) for two strains Bacillus stearothermophilus and Bacillus subtilis. The results showed antibiotic residue contamination in 18.12% of samples. Tetracycline and/or penicillin residues were responsible for the contamination of 90% of positive milk samples, while macrolide and/or aminoglycoside residues were only detected in 6.66% of positive samples. The confirmation by the agar diffusion test of the 31 raw milk samples including 30 positive and one suspicious sample, analysed by the acidification test, showed a contamination rate of 90.32% for beta-lactams and/or tetracyclines (28 samples) and a contamination rate of 3.22% for aminoglycosides and/or macrolides (2 samples). The suspicious sample tested negative. The results of this study showed that the control and monitoring of antibiotics and their residues by collectors and in foods of animal origin are particularly important to ensure the safety of food of animal origin, and thus to protect the consumer.